Effect of different factors on the yield of epoxy-terminated polydimethylsiloxane and evaluation of CO2 thickening. Issue 70 (29th November 2018) - Wang, Yanling; Li, Qiang; Dong, Weihong; Li, Qingchao; Wang, Fuling; Bai, Hao; Zhang, Ren; Owusu, Augustus Boadi
Abstract : We focused on optimizing synthetic parameters based on a Taguchi design to maximize polymer yield and evaluate the polymer-thickening ability in CO2 . Abstract : We focused on optimizing synthetic parameters based on a Taguchi design to maximize polymer yield and evaluate the polymer-thickening ability in CO2 . The stirring speed, reaction temperature, catalyst content, and reaction time were the major control parameters (independent variables) in these two individual reactions. The signal-to-noise ratio (S/N ratio) obtained under each experimental condition was utilized to evaluate the optimum preparation process for the maximum yield. A maximum yield of 87.20% in a ring-opening polymerization was reported, and the optimum conditions were 70 °C, 2.0 g of sulfuric acid, and stirring speed of 110 rpm. Temperature, however, was the most effective factor. Similarly, research of hydrosilylation obtained a maximum yield of 84.7% under optimum conditions of 100 °C, chloroplatinic acid of 0.003 wt%, and stirring speed of 190 rpm. Also, we measured CO2 viscosity based on different concentrations of thickener at different temperatures, pressures and flow rates. Epoxy-terminated polydimethylsiloxane could be used for CO2 fracturing to obtain excellent fracturing.